EVALUATION OF WRITING SKILLS AND STRATEGIES IN 3RD SEMESTER STUDENTS OF UMMUBA'S ENGLISH EDUCATION DEPARTMENT - Aura, Dhea (Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT This research employed a quantitative approach to determine the extent of students' self-assessment regarding writing abilities and strategies used by third- semester students in the English Language Education Department at UMMUBA. A survey method using questionnaires was utilized to gather data on confidence levels in writing, understanding of writing strategies encompassing general writing strategies, pre-writing strategies, during-writing strategies, and post-writing strategies. Statistical analysis will be conducted to interpret survey data and draw conclusions regarding the evaluated aspects. This research is expected to provide a deeper understanding of the actual quantitative conditions regarding writing abilities and strategies used by third-semester students in the English Education Program Study at UMMUBA. Keyword: Writing Skill’s, Strategies, Self-Assessment